2014
DOI: 10.1002/biof.1174
|View full text |Cite
|
Sign up to set email alerts
|

Can proline‐rich polypeptide complex mimic the effect of nerve growth factor?

Abstract: Naturally occurring compounds that can act as prosurvival factors and neurite formation stimulants in the conditions of reduced neurotrophins production are important both in neuronal protection and therapy of neurodegenerative disorders. Therefore, the role of proline-rich polypeptide complex (PRP) and its nonapeptide fragment (NP) in the promotion of pheochromocytoma cell line (PC12) survival and neurite outgrowth pathway is presented. It was shown that PRP/NP did not affect the neuronal nitric oxide synthas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…NGF synthesis in primary astrocytes is connected with ERK 1/2 MAP kinase activation as was shown by Xu et al ( 2013 ) and Park et al ( 2006 ). In our previous work, it was shown that PRP is able to activate ERK 1/2 MAP kinases (Zabłocka et al 2014 ). We can suppose that an increased level of βNGF may be also connected with the ability of the PRP complex to activate the ERK1/2 kinase signaling pathway or with the effect of PRP on NGF release to the extracellular space (Lessmann et al 2003 ; Reichardt 2006 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…NGF synthesis in primary astrocytes is connected with ERK 1/2 MAP kinase activation as was shown by Xu et al ( 2013 ) and Park et al ( 2006 ). In our previous work, it was shown that PRP is able to activate ERK 1/2 MAP kinases (Zabłocka et al 2014 ). We can suppose that an increased level of βNGF may be also connected with the ability of the PRP complex to activate the ERK1/2 kinase signaling pathway or with the effect of PRP on NGF release to the extracellular space (Lessmann et al 2003 ; Reichardt 2006 ).…”
Section: Discussionmentioning
confidence: 98%
“…Immortalized cell lines with astrocyte-like morphology such as U87, U373, or 1321N1 originally derived from human malignant tumors constitute relatively good model system for astrocytes in vitro because of their functional similarity to normal astrocytes (Wagoner et al 1999 ; Nishiguchi et al 2003 ; Wong et al 2010 ; Yoshida et al 2011 ; Saeed et al 2015 ). During previous studies on the proline-rich polypeptide complex (PRP), activities were shown that both PRP complex and its nonapeptide fragment NP at low doses ranging from 0.01 to 10 μg/ml increase neuronal survival stimulate neuronal proliferation and induce neuritogenesis of PC12 cells (Basci et al 2005 ; Schuster et al 2005 ; Bourhim et al 2007 ; Douraghi-Zadeh et al 2009 ; Zabłocka et al 2014 ). Based on published results obtained on human astrocytoma cell lines used to examine the molecular signaling and mechanisms connected with protection of neuronal cells (Wagoner et al 1999 ; Deb et al 1999 ; Nischiguchi et all., 1999; Mori et al 2008 ; Wang et al 2010a , b ; Yoshida et al 2011 ; Li et al 2014 ; Saeed et al 2015 ), the purpose of the present study was to investigate the ability of proline-rich polypeptide complex PRP and its nonapeptide fragment NP to up-regulate the secretion of neurotrophins on the model of human astrocytoma cell line U87.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very important activity of PRP is the prevention of Aβ aggregation and the disruption of aggregates already existing (Schuster et al 2005;Janusz et al 2009). PRP increases neurite outgrowth in a dose-dependent manner as demonstrated in a cell differentiation model system of pheochromocytoma PC12 cells (Basci et al 2005;Zabłocka et al 2014). PRP is considered as a promising pharmacological agent, due to its ability to suppress uncontrolled microglial activation.…”
Section: Introductionmentioning
confidence: 99%
“…It modulates the innate immune response, including phagocytosis and the balance between oxidants and antioxidants, thus regulating redox-sensitive cellular signaling [ 23 25 ]. Additionally, PRP can affect learning, memory, and lifespan and possesses neuroprotective activity [ 23 , 26 , 27 ]. The activity of PRP suggests a potential therapeutic use in the case of diseases associated with changes in innate immunity, for example, Alzheimer's disease [ 23 ].…”
Section: Introductionmentioning
confidence: 99%